Role of Nitrogen‐Doped Carbon Nanofibers Inside Polymer Membranes for Enhancing Fuel Cell Performance. Issue 6 (19th April 2018) - Jang, Jeongsoek; Lee, Jin Goo; Hwang, Ho Jung; Kwon, Ohchan; Jeon, Ok Sung; Ji, Yunseong; Shul, Yong Gun
Abstract : Role‐playing : The pseudo‐capacitive behavior of a membrane reinforced by nitrogen‐doped carbon nanofibers (N‐CNF) reduces the charge‐transfer resistances in polymer electrolyte membrane fuel cells (PEMFCs), which, in turn, enhances their power density.